THE EFFECT OF MULTIMEDIA TOOLS ON VOCABULARY ACQUISITION AMONG ESL LEARNERS - Jovliyeva Nafosat Bahodir qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Annotation: This article investigates the impact of multimedia tools on vocabulary acquisition among learners of English as a second language (ESL). The study emphasizes the role of visual, auditory, and interactive materials in enhancing learners’ word recognition, retention, and contextual understanding. Multimedia tools such as videos, animations, online games, and digital flashcards create a dynamic and engaging learning environment that supports both explicit and implicit vocabulary learning. The findings suggest that integrating multimedia resources into English lessons increases motivation, improves memory recall, and facilitates long-term vocabulary mastery.